Phenolic Composition, Browning Susceptibility, and Carotenoid Content of Several Apricot Cultivars at Maturity - Mohsen Radi; Mostafa Mahrouz; Abderrahim Jaouad; M. Tacchini; S. Aubert; MIREILLE HUGUES; Marie Josèphe Amiot (1997)
Phenolic composition and susceptibility to browning were determined for nine apricot ( Prunus armeniaca L.) cultivars. Chlorogenic and neochlorogenic acids, (+)-catechin and (-)-epicatechin, and rutin (or quercetin-3-rutinoside) were the major phenolic compounds in apricots. In addition to these compounds, other quercetin-3-glycosides and procyanidins have been detected. Chlorogenic acid content decreased rapidly during enzymatic browning, but the susceptibility to browning seemed to be more strongly correlated with the initial amount of flavan-3-ols (defined as catechin monomers and procyanidins). As chlorogenic acid is certainly the best substrate for polyphenol oxidase, the development of brown pigments depended mainly on the flavan-3-ol content.